Pertumbuhan Vegetatif Sayuran Indigenous Daun Walang Liar (Eryngium foetidum) Pada Beberapa Kombinasi Perlakuan Jenis Media Tanam dan Dosis Pupuk - Pribadi, Edi Minaji; Azmi, Tubagus Kiki Kawakibi (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2019)
Culantro (Eryngium foetidum) can be found grow wild in some areas in West Java, one of them is in Cisarua, and it has been used for the community as salad. However, this indigenous vegetables rarely seen in vegetable markets in the area, since it is not cultivated. This need attention for its conservation and sustainability in the market. One of the efforts can be done is to cultivate them in the appropriate growth environment. Type of growing media and fertilizer are important aspects in vegetables cultivation. This research aimed to find the optimum combination of growing media with fertilizer dose for wild culantro vegetative growth. Based on the research, vegetative growth which measured by length and number of leaf cumulatively during observation 7 month after transplanting showed significantly different (Î± = 1%). The best vegetative growth obtained on the combination of husk charcoal media with 1000 ppm Grow More (32:10:10), resulting in length and number of leaf were 19,41 cm and 14,10 respectively.